MODELING OF ELECTROMAGNETIC DEVICES FOR MEASURING ASYMMETRIC REACTIVE POWER CURRENT PROCESSES IN A HYBRID POWER SUPPLY SYSTEM NETWORK - A. B. Abubakirov (Modern American Journals, 2025)
This article presents the modeling of reactive power currents in hybrid energy source electrical supply systems using primary asymmetric processes, employing collected and distributed parameter graph models as well as analytical expressions to ensure high accuracy for electromagnetic devices.
Keywords: Reactive power, graph model, modeling, electromagnetic device, electrical supply, analytical expression.